The Effect of Field Work Practices, Career Guidance, and Emotional Intelligence through Work Interest on Work Readiness (Journal of Economic Education, 2022)
Work readiness is a set of skills and behaviours needed to work and is indispensable to get maximum results according to the expected target. The purpose of this study was to analyze the effect of field work practices, career guidance, and emotional intelligence through work interest on students’ work readiness. The type of this study was quantitative research. The population of this study was 626 students of class XII of the Public Vocational Schools for the Business Management program in Semarang City with a sample of 140 students. The data were collected using a questionnaire that has been tested for validity and reliability. The data analysis used descriptive statistics, path analysis, and single test. The research results showed that field work practices had no effect on work interest. Career guidance had a positive and significant effect on work interest by 17.05%. Emotional intelligence had a positive and significant effect on work interest by 23.23%. Field work practices through work interest had no effect on work readiness. The total effect of career guidance through work interest on work readiness was 37.15%. The total effect of emotional intelligence through work interest on work readiness was 15.97%. Work interest had a positive and significant effect on work readiness by 10.89%.